Bridging the rural-urban divide in developing countries : SBI Youth for India model - Mukherjee, Kajari; Bhatta, N. M. K. (London : NeilsonJournals Publishing, 2018)
Several volunteer projects have been designed and put to use in developing countries in an attempt to narrow the rural-urban divide. In most, people from developed economies worked in developing countries on projects typically designed to improve health and educational facilities. While these initiatives received some degree of success in homogeneous countries for example, in Africa and Latin America, they were of limited use in a heterogeneous country like India with its multiple cultures and multiple languages. It became clear that it would be better for India to use its own citizens for volunteer work in rural communities. India's largest Public Sector Bank, the State Bank of India (SBI) therefore initiated a rural fellowship program called SBI Youth for India (YFI) in 2010 to encourage the educated young to contribute to bridging the rural-urban divide. As opposed to other volunteer models, YFI had the potential to be readily replicated as it was resource-thin yet impact-heavy. This case study describes the conceptualisation and implementation of YFI and the challenges it faced in its initial years. The challenge for students is how to scale up the program more widely in India and for other developing countries to take note and replicate.
Originally Published In Mukherjee, K., & Bhatta, N. (2018). Bridging the Rural-Urban Divide in Developing Countries: SBI Youth for India Model. Journal of International Business Education, 13(1), 381-402. JIBE13-0CS8.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Rural development projects -- India -- Case studies